A systematic review and quantitative analysis of different therapies for pancreas divisum - Hafezi, Mohammadreza; Mayschak, Bartosch; Probst, Pascal; Büchler, Markus W.; Hackert, Thilo; Mehrabi, Arianeb (The American journal of surgery, 2017)
Background Pancreas divisum is the most common anatomical variation of pancreatic ductal system affecting 5-10% of population. Therapy includes different endoscopic and surgical procedures. The aim of this article was to summarize actual evidence of different treatment. Methods A Medline search was performed to identify all studies, investigating endoscopic or surgical therapy of Pancreas divisum. An individual data simulation model was applied to compare endoscopic and surgical studies. Result 56 observational studies (31 endoscopic and 25 surgical studies) were included in analyses. Surgery was significantly superior to endoscopic treatment in terms of success rate (72% vs. 62.3), complication rate (23.8% vs. 31.3%) and re-intervention rate (14.4% vs. 28.3%). Conclusion Surgery may be superior to endoscopy in terms of treatment success and complications. There is no study comparing these two therapies. Consequently, a randomized trial is needed to clarify if endoscopy or surgery is superior in the therapy of pancreas divisum.